Question #f5be3

1 Answer
Feb 9, 2016

O = 4

Explanation:

Solution:

We have,
Average of m, n ,p = 12
i.e. bar X = 12
Then using the formula to calculate the average we have,
(m+n+p)/3 = 12
or (m+n+p)/3 * 3 = 12 *3 [Multiplying both sides by 3 ]
or m+n+p = 36

Now,
For the mean of m, n , o ,p
We have
bar X_1 = 10
So,
bar X_1 = (m+n+ o +p)/4
or 10 = (m+n+ p)/4 + (o)/4
From above We have m+n+p = 36
Putting its value we get
10 = 36/4 + (o)/4
10 = 9 + (o)/4
10 -9= 9- 9 + (o)/4 [ Subtracting both sides by 9]
1 = o/4
1*4 = o/4*4 [Multiplying both sides by 4]
o=4
Thus,
O = 4